SEJARAH MASJID AGUNG AL HUDA DI TEMBILAHAN KABUPATEN INDRAGIRI HILIR TAHUN 1900-2018 - M. Ridwan M. Ridwan; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Mosque is a form of Islamic culture that rich in scientific knowledge. Mosque is a a sign, symbol, orientasion of the existence of Islam and its people. The definition of mosque in terms of etymology is a place of prostrasion, but the function of the mosque is not only a place of prostrasion to Allah but also a place of activity that is relationship between human beings. The Purpose of this studies is (1) to find out the history of Grand Al Huda Mosque establishment (2) to find out the characteristics of Grand Al Huda Mosque buildings (3) to find out organizational structure of the Grand Al Huda Mosque (4) to find out the role of Grand Al Huda Mosque in educational field. Grand Al Huda Mosque is the first Mosque in Tembilahan area. the history of the establishment of the mosque is inseparable from the development of Islam and the people in the Tembilahan area, This mosque was founded around the mid-1920s. With the initial construction of wooden buildings using ironwood roofs. Along with population growth and the need for larger mosques, a renovation of the mosque was carried out. The first renovation was carried out in 1935 without changing the initial shape of the building. The second renovation the Al Huda Grand Mosque was carried out in 1968 by changing the entire form of the initial building but the mosque building was still in a semi-permanent form. In 1994 the third renovation was carried out by transforming mosque buildings into permanent buildings. The Grand Al Huda Mosque was inaugurated by the Indragiri Hilir regent, H. Azwin Yacub on 12 June 1999. The function of Al Huda Grand Mosque not only as a place of worship but also as a place for organizing and educational functions.Key Words: History, Mosque, Tembilahan